Analisis Efektivitas Digital Marketing dalam Meningkatkan Minat Nasabah pada Perbankan Syariah - Noviana, Susi; Haryanti, Peni (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
The development of Islamic banking in Indonesia faces challenges in attracting customers, especially younger generations who are more familiar with digital technology. Digital marketing has become an important strategy for reaching a wider market segment through social media, websites, and mobile applications. This study uses a literature review method to analyze the effectiveness of digital marketing in increasing customer interest in Islamic banking. The results of the study show that educational, interactive, and transparent digital marketing can increase customer awareness, trust, and emotional attachment to Islamic products. The factors for the success of this strategy include content quality, ease of access to digital services, content segmentation according to customer profiles, and multichannel communication integration. However, the effectiveness of digital marketing is still limited by the scarcity of educational content, human resource capacity, and the level of digital literacy among the public. This study concludes that optimizing creative, personalized, and educational digital marketing strategies is key for Islamic banking to increase customer interest and loyalty.